PENERAPAN METODE BERCERITA ISLAMI DALAM MENANAMKAN KARAKTER MANDIRI BELAJAR PADA ANAK KELOMPOK A DI RA SABILLILAH WAJAK-MALANG - Ida Yuliati (Program Studi Pendidikan Islam Anak Usia Dini (PIAUD), 2025)
The application of Islamic-based storytelling methods in instilling characters in children has benefits in every storytelling technique including storytelling techniques through smart hafiz media, hand puppets, illustrated picture story books, and two-way communication. The research method used is qualitative-descriptive in data collection techniques including observation, interviews/needed field data, and documentation. The findings of the study include storytelling techniques in early childhood learning that have an influence on the meaningfulness of children in understanding the storyline, such as storytelling techniques through smart hafiz providing audio-visual story material based on the media version. Then, if using the hand puppet technique certainly has advantages in terms of exploratory use. However, the disadvantage of hand puppet media as a mediator for children in storytelling needs to have many varied roles/characters. Illustrated picture story book media has almost the same advantages and disadvantages in terms of provision and use. Meanwhile, storytelling techniques through two-way communication have the advantage that children can tell stories using their own language without narration and emphasis. Thus, children can tell stories with a sense of comfort, safety and depth. The story topic is in accordance with the creativity that arises in the child's mind at that time. The disadvantage of the two-way communication technique is that it takes a long time to implement. As communicators, educators play a crucial role in generating engaging story topics. Character development through four storytelling techniques includes independent learning, friendly/communicative behavior, a love of reading, and democratic learning.